LEGISLASI DAERAH YANG PARTISIPATIF - Tomy Michael (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2012)
Regional government, in fact often demonstrated an inability to generate local regulations in legislative program. This is because of political interaction in the rulemaking. To overcome this problem, among others, the local government form regulations regarding the procedure for the preparation and management of Prolegda in the form of Regional Head Regulation and Parliament Regulation with reference to the Law No. 12 of 2011 and Presidential Regulation No. 61 of 2005, to make the ideas of the academic community who are competent in law legislation.